PERAN PERPUSTAKAAN DIGITAL UPN “VETERAN” JAWA TIMUR DALAM MEMENUHI KEBUTUHAN LITERASI MAHASISWA SELAMA KULIAH DARING - Andika Maulana; Ananta Prathama (Universitas Halu Oleo, 2021)
The COVID-19 pandemic occurred in various parts of the country, one of which was Indonesia, which was also affected. In order to prevent the transmission from getting bigger, people's activities from various sectors are limited. Such as the tourism sector and the economic sector are the most affected, because many employees who are laid off have the potential to generate a lot of new unemployment. The education sector is also not spared from these restrictions. For example, lecture activities are still limited to being held directly. Libraries play an important role in the learning process. In normal face-to-face lectures, students ideally spend more lecture time in the library, compared to face-to-face with lecturers in class. Especially in the online lecture system, where students definitely need the role of the library as a means to deepen the material received. This study has a purpose, namely to find out the role of the digital library of UPN